THE EFFECT OF LABOR FORCE PARTICIPATION, PER CAPITA INCOME, AND INDUSTRIALIZATION ON URBANIZATION IN INDONESIA - Reza Juanda; Khalimatusakdiah (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of labor force participation, per capita income, and industrialization on urbanization in Indonesia in the short and long term. Rapid urban growth poses various social and environmental challenges. This study uses secondary data from the 1991–2023 time series and analyzes it using the Autoregressive Distributed Lag (ARDL) model to examine the dynamic relationships between variables. The results show that labor force participation has a significant effect on urbanization in the short term, although the direction of the influence is inconsistent. In the long term, the influence is insignificant. Per capita income also has a significant effect in the short term with varying directions, but is insignificant in the long term. Industrialization shows a negative effect in the current period and a positive effect in the previous period, but its long-term effect is also insignificant. Simultaneously, all three variables have a significant effect on urbanization in the short term, but not in the long term. These findings indicate that urbanization in Indonesia is more influenced by short-term socioeconomic dynamics than long-term structural factors.